Treatment of ovaries atrophy in heifers and cows- I. Treatment of of ovaries atrophy with pregnant mare’s serum gonadotropin or human chorionic gonadotropin - ΣΕΙΤΑΡΙΔΗΣ Κ.; ΣΤΡΑΒΑΡΙΔΗΣ Μ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The results of ovaries atrophy treatment by I.V. injection of 1000 I.U pregnant mare’s serum gonadotropin (PMSG) or 1000 I.U human chorionic gonadotropin (HCG) in 34 heifers and 33 cows, are described. 16 out of 22 heifers, that is 72.7% treated with PMSG and 50% of the 12 heifers treated with HCG had oestrus 21 days post injection. Pregnancy after the first insemination was 40.9% and 41.7% respectively. 13 out of 18 cows, that is 72.2%, treated with PMSG and 12 out of 15 cows, that is 80%, treated with HCG had oestrus 21 days post injection. Pregnancy after the first insemination was 66.7% and 80.0% respectively. Totally from 40 heifers and cows treated with PMSG 72.0% had oestrus and 52.0% were pregnant while 27 heifers and cows treated with HCG 66.3% had oestrus and 62.9% were pregnant. These differences are not statistically significant